KONTRIBUSI M. SYUHUDI ISMAIL DALAM KONTEKSTUALISASI PEMAHAMAN HADIS - Amrulloh, Amrulloh (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2017)
This article deals with the contextual understanding of Syuhudi Ismail to the ?adîth. Syuhudi is one of the inspired Indonesian Muslim scholars who has high attention to the study of hadîth. His work entitled Hadis Nabi yang Tekstual dan Kontekstual: Telaah Ma?anil Hadis tentang Ajaran Islam yang Universal, Temporal dan Lokal, has been considered as one of the most valuable contributions in promoting the dynamic, progressive and universal understanding of Islam. By applying descriptive-comparative analysis and contextual approach, this article finds that Syuhudi?s contributions in formulating the concept and practice of contextual understanding of the ?adîth are quite different from other Muslim scholars. This is due to the basic assumption of Syuhudi?s understanding that the prophet has several roles at the mean time, the necessity of applying universal value of Islam, and the actual change of the society. This, in turn, brings Syuhudi?s contextual understanding into the idea of differentiated meanings of the ?adîth which are universal, local and temporal.